Do Different Casein Concentrations Increase the Adverse Effect of Rutin on the Biology of Anticarsia gemmatalis Hubner (Lepidoptera: Noctuidae)? - Salvador, Mariana C. [UNESP]; Boica, Arlindo L. [UNESP]; de Oliveira, Maria C. N.; da Graca, Jose P. [UNESP]; da Silva, Debora M.; Hoffmann-Campo, Clara B. (Entomological Soc Brasil, 2010)
The flavonoid rutin is recognized as playing an important role in the protection of plants against lepidopterans. Bioassays with this compound are generally carried out using artificial diets. Proteins of high energy value, such as casein, are important ingredients of insect artificial diets as a source of essential amino acids. However, such proteins can generally increase the allelochemical activity. Our objective was to evaluate the effects of rutin on larvae of the velvetbean caterpillar Anticarsia gemmatalis Hubner by incorporating this allelochemical into diets with different concentrations of casein. Three casein concentrations (0, 7 g, or 14 g) combined with none, 0.65%, or 1.30% of rutin were added to the rearing diet and offered to the larvae from hatching to pupation. Rutin negatively affected larval development, the amount of food consumed, and pupal weight of A. gemmatalis. These negative effects were clearly seen in insects fed on diets with 7 g of casein to which any concentration of rutin was added. The effects of rutin when added to the diets without casein were stronger than in diets containing a suitable amount of casein (14 g). The greater negative effects of rutin in diets containing suboptimal concentrations of casein indicate that casein can increase the effects of rutin only when the diets are nutritionally unsuitable for insect development.
Keywords: Flavonoid; velvetbean caterpillar; biological parameter